(untitled) (Eurasian Scientific Herald, 2022)
This article discusses modern pedagogical technologies in teaching biology. At present, a new education system is being formed in Uzbekistan, focused on entering the world educational space. This process is accompanied by significant changes in the pedagogical theory and practice of the educational process.